Targeted therapy for head and neck squamous cell carcinoma microenvironment - Guo, Zhaomeng; Li, Kang; Liu, Peng; Zhang, Xiangmin; Lv, Jie; Zeng, Xianhai; Zhang, Peng (Frontiers in Medicine, 2023)
Head and neck squamous cell carcinoma (HNSCC) originates from the squamous epithelium of the oral cavity, oropharynx, larynx, and hypopharynx. HNSCC in the oral cavity and larynx is strongly associated with tobacco smoking and alcohol consumption, while oropharyngeal cancer is increasingly attributed to infection by human papillomavirus (HPV), particularly HPV-16. The tumor microenvironment (TME) is a complex network of cancer cells, immune cells, stromal cells, surrounding blood vessels, and signaling molecules, and plays a critical role in tumor cell survival, invasion, and recurrence. Therefore, it is critical to elucidate the molecular basis of the interaction between tumor cells and the TME in order to develop innovative anti-cancer therapeutic strategies.